2021
DOI: 10.1111/jcpt.13469
|View full text |Cite
|
Sign up to set email alerts
|

Impact of corticosteroid use on outcomes of non–small‐cell lung cancer patients treated with immune checkpoint inhibitors: A systematic review and meta‐analysis

Abstract: What is known and objective Administration of corticosteroids to immune checkpoint inhibitors (ICI)–treated patients has raised concerns due to doubts about ICIs' efficacy under those conditions. Hence, we reviewed studies comparing overall and progression‐free survival (OS and PFS) outcomes in patients with non–small‐cell lung carcinoma (NSCLC) treated with ICI and either with or without corticosteroids for any reason. Methods We searched the PubMed Central, Cochrane library, EMBASE and MEDLINE databases from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…They are commonly used by patients with cancer and transplant recipients, making immunosuppression-induced dysbiosis a topic of research in transplant settings (Colard-Thomas et al 2023 ; Chong and Koh 2020 ). Some meta-analyses have reported negative effects of CSs on the survival of patients treated with ICIs (Petrelli et al 2020 ; Zhang et al 2021 ). It should be noted that patients requiring high doses of steroids, such as those with palliative reasons or brain metastases, may have pre-existing conditions that make them vulnerable to poor prognoses, which could be a confounding factor that cannot be excluded (Jessurun et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…They are commonly used by patients with cancer and transplant recipients, making immunosuppression-induced dysbiosis a topic of research in transplant settings (Colard-Thomas et al 2023 ; Chong and Koh 2020 ). Some meta-analyses have reported negative effects of CSs on the survival of patients treated with ICIs (Petrelli et al 2020 ; Zhang et al 2021 ). It should be noted that patients requiring high doses of steroids, such as those with palliative reasons or brain metastases, may have pre-existing conditions that make them vulnerable to poor prognoses, which could be a confounding factor that cannot be excluded (Jessurun et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since only two studies have discussed the use of immunosuppressants to control irAEs, we cannot rely on the limited data to accurately analyze results [15,19] . Zhang et al found that the OS and PFS were signi cantly shortened in the administration of corticosteroids [32] . However, Fausto et al indicated that the use of steroids in cancer patients to control irAEs did not shorten OS [33,34] .…”
Section: Discussionmentioning
confidence: 99%
“…One study noted that even an average of 6 days of oral corticosteroids (maximal dose, 40 mg/day) was associated with an increased incidence of diabetes mellitus, sepsis, venous thromboembolism, and fractures ( 52 ). Furthermore, a meta-analysis suggested that corticosteroids may also blunt the efficacy of ICPIs in patients with non-small cell lung cancer ( 53 ). Premature discontinuation of ICPI therapy without confirmatory testing can negatively impact treatment outcomes by halting a potentially life-saving treatment.…”
Section: Role Of Kidney Biopsy In Icpi-akimentioning
confidence: 99%